The effect of family-centered empowerment model on quality of life and self-efficacy of kidney transplant patients in 2018 - Ramin Dastab; Farahnaz Farnia; Somayeh Zare (Tehran University of Medical Sciences, 2020)
Background: Quality of life is a mental issue that causes a person to be affected by various factors including self-efficacy. The roadmap in this field is family-centered empowerment, which aims to promote health. The aim of this study was to determine the effect of family-centered empowerment model on quality of life and self-efficacy of kidney transplant patients. Materials and Method: This study is a randomized controlled clinical trial. 100 kidney transplant patients, who came to Shahid Hasheminejad Hospital, were divided into two groups of control and intervention by initial accidental sampling. Data collection tools were a three-part questionnaire includes of demographic characteristics, quality of life of patients of kidney transplant questionnaire (KTQ-25) and the questionnaire of health empowerment to survey about self-care (SUPPH). These questionnaires were completed by both groups once the study was initiated and another time 1.5 months after intervention. Data were analyzed by SPSS software (version 20), chi-square and T-test. Results: findings demonstrated that when the study was initiated there was not any significance difference between these two groups in terms of demographic quantitative and qualitative characteristics and mean of quality of life and self-efficacy. In compared with control group, mean of quality of life of intervention group was increased. Statistically, it has a significance difference (0<0.001). Also, in comparison with control group, the score of self-efficacy promoted and it has a significance difference. Conclusion: Considering the positive effect of family-centered empowerment model on self-efficacy of kidney transplant patients and finally on their quality of life, it is necessary to consider this model with the aim of promoting patientschr('39') health.